SERANGAN HAMA PENGGEREK BATANG PADI KUNING (Scirpophaga incertulas Wlk.) PADA TANAMAN PADI SAWAH (Oryza sativa L.) di DESA LIWUTUNG II KECAMATAN PASAN KABUPATEN MINAHASA TENGGARA - Olden Julio Ronaldy Uguy; Vivi Montong; James Kaligis (COCOS, 2020)
ABSTRAKRice plants (Oryza sativa L.), including the Poaceae family, one of the most important food plants forIndonesia because the staple food for most of the population is rice. Scircpophaga incertulas (Yellow PBP) isone of the most harmful rice plant pests in Indonesia and several countries in Asia. This study aims todetermine the level of attack of the Yellow Rice Stem Borer in rice (Oryza sativa L.), especially in LiwutungII Village, Pasan District, Southeast Minahasa Regency. The research was conducted in Liwutung II Village,Pasan District, Southeast Minahasa Regency. The research was conducted from September to December2020. The materials and tools used were rice plants, tajar gamal wood, scissors, plastic rope, tweezers,cameras and ATMs. The study used a survey method in lowland rice fields in the generative phase in 3different rice fields with five sub-plots, each sub-plot was taken 50 clumps of plants to be observed. The areaof the rice plot used is A (60 x 5 m) B (60 x 7 m) C (30 x 5 m). Sub plot (3 x 3 m). The things observed werethe number of S. incertulas infestations found in each sub-plot and the number of clumps attacked. Based onthe research that has been done, it can be concluded that the most attacks were in rice field B with an attackintensity of 15.4%, rice field A 14.9% and the lowest attack intensity was found in rice field C with anaverage attack intensity of 5.4. %Keywords: Yellow Rice Stem Borer Attack